2003
DOI: 10.21273/hortsci.38.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diurnal Temperature on Nutrient Release Patterns of Three Polymer-coated Fertilizers

Abstract: This study was conducted to determine the effects of temperature on nutrient release patterns of three polymer-coated fertilizers (PCFs), each using a different coating technology: Osmocote Plus 15N-3.93P-9.96K, Polyon 18N-2.62P-9.96K, and Nutricote 18N-2.62P-6.64K. Each fertilizer was placed in a sand-filled column and leached with distilled water at ≈100 mL·h-1, while being subjected to a simulated diurnal container temperature change from 20 to 40 °C and back to 20 °C over a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 5 publications
7
27
1
Order By: Relevance
“…is consistent with previous findings (Husby, 2000;Jacobs, 2005;Adams et al, 2013). For example, Adams et al (2013) found that total NH 3 and NO 3 À were >70% expended while PO 4 3À was <60% expended after 9 months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…is consistent with previous findings (Husby, 2000;Jacobs, 2005;Adams et al, 2013). For example, Adams et al (2013) found that total NH 3 and NO 3 À were >70% expended while PO 4 3À was <60% expended after 9 months.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in temperature commonly results in increased nutrient release from polymer-coated fertilisers (Husby, 2000;Jacobs, 2005;Du et al, 2006;Adams et al, 2013). In this study and others, Polyon™ clearly demonstrates faster release of NePeK at 23 C compared to 4 C (Adams et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…However, there is no consensus on the effect of temperature on PCF collectively or on individual PCF technologies in the recent literature. Husby et al (2003) claimed that the effect of a diurnal temperature fluctuation on nutrient-release rate was a sensational 63.9% to 206.2% per°C (1278% to 4124% in total), depending on the PCF (Osmocote, Nutricote, and Polyon) when temperature was varied between 20°C and 40°C. Husby et al (2003) reported that Osmocote was the most sensitive to temperature of the three technologies.…”
Section: Environmental Effects On Nutrient Releasementioning
confidence: 99%
“…Husby et al (2003) claimed that the effect of a diurnal temperature fluctuation on nutrient-release rate was a sensational 63.9% to 206.2% per°C (1278% to 4124% in total), depending on the PCF (Osmocote, Nutricote, and Polyon) when temperature was varied between 20°C and 40°C. Husby et al (2003) reported that Osmocote was the most sensitive to temperature of the three technologies. Cabrera (1997) reported significant increases in N leaching as media temperature increased in pots of media containing Prokote ® , a Polyon, and two Osmocote fertilizers (High Nitrogen and Fast Start).…”
Section: Environmental Effects On Nutrient Releasementioning
confidence: 99%
“…A laboratory method is crucial to quantify differences between commonly used fertilizers and slow release ones under controlled conditions to provide an understanding of the mode of action of the release at varying stages of development. In recent years, for example, with polymer chemistry advancements, several polymer coated fertilizers have been produced, the nutrient release curves for which vary with temperature and time ( Husby , ). Trenkel () pointed out that some have been developed with a parabolic, sigmoidal or linear nutrient release, with the latter two shown to better match plant demand.…”
Section: Discussionmentioning
confidence: 99%